Genes Involved in the Production of Antimetabolite Toxins by Pseudomonas syringae Pathovars. - Arrebola-Díez, Eva María; Cazorla-López, Francisco Manuel; Pérez-García, Alejandro; De-Vicente-Moreno, Antonio (MDPI, 2011)
Pseudomonas syringae is pathogenic in a wide variety of plants, causing diseases with economic impacts. Pseudomonas syringae pathovars produce several toxins that can function as virulence factors and contribute to disease symptoms. These virulence factors include antimetabolite toxins, such as tabtoxin, phaseolotoxin and mangotoxin, which target enzymes in the pathways of amino acid metabolism. The antimetabolite toxins are generally located in gene clusters present in the flexible genomes of specific strains. These gene clusters are typically present in blocks of genes that appear to be integrated into specific sites in the P. syringae core genome. A general overview of the genetic organization and biosynthetic and regulatory functions of these genetic traits of the antimetabolite toxins will be given in the present work.
Keywords: Pseudomonas syringae; Bacterias fitopatógenas; Antimetabolitos; Plantas - Enfermedades y plagas; Secondary metabolite; Gene cluster; Tabtoxin; Phaseolotoxin; Mangotoxin; Phytotoxin